Leggere il teatro (Materiali di Estetica. Terza serie, 2022)
The theatrical work of Maddalena Mazzocut-Mis, published in the volume Teatro da leggere. Mito e conflitto – with the accompaniment of detailed premises by the author herself – develops in two directions. The first one, looking at the past, leads to the rewriting of works of the literary tradition according to a new point of view. The reworking of famous classical characters relates the distant with the near, allowing us to reflect, among other things, on the function and value of illusions. The second, looking at the present, leads to the presentation of seemingly insignificant characters to highlight the tragic fate of rise and fall or desperate search for a recognized identity.
Keywords: Theatre; Myth; Rewriting